Bacteria and Archaea biodiversity in Arctic terrestrial ecosystems affected by climate change in Northern Siberia - Barret, Maialen; Thalasso, Frederic; Gandois, Laure; Cruz, Karla Martinez; Jaureguy, Armando Sepulveda; C?Line Lavergne; Teisserenc, Roman; Polette Aguilar; Gerardo-Nieto, Oscar; Etchebehere, Claudia; Martins, Bruna; Fochesatto, Javier; et al. (SCAR - Microbial Antarctic Resource System, 2019)
Methane emissions from aquatic and terrestrial ecosystems play a crucial role in global warming, which is particularly affecting high-latitude ecosystems. As major contributors to methane emissions in natural environments, the microbial communities involved in methane production and oxidation deserve a special attention. Microbial diversity and activity are expected to be strongly affected by the already observed (and further predicted) temperature increase in high-latitude ecosystems, eventually resulting in disrupted feedback methane emissions. The METHANOBASE project has been designed to investigate the intricate relations between microbial diversity and methane emissions in Arctic, Subarctic and Subantarctic ecosystems, under natural (baseline) conditions and in response to simulated temperature increments. We report here a small subunit ribosomal RNA (16S rRNA) analysis of lake, peatland and mineral soil ecosystems.